WAVE NUMERICAL MODEL OF SWELL AND SEA AT ROTE STRAIT - Satria Damarnegara; Fuddoly Fuddoly; Dyah I Widyastuti (Journal of Civil Engineering, 2020)
A spectral wave numerical simulation based on SWAN is used to model 10 years wave climate at Rote Strait, NusaTenggara Timur province. ERA5 reanalysis data of total wave and wind is used for model forcing. Simulation results showwaves direction in Rote strait are coming from southeast and southwest. Waves direction at nearshore of southeast Timor islandcoast are coming from southeast because of refraction and diffraction. Waves height over 0.8 m occurs in 320 days in one year.50 years wave return period calculated at 2.68 m height. Indeed, port development in Rote strait area need to consider the downtime caused by waves and extreme wave forces in the design.